An adaptive isogeometric shell element for the prediction of initiation and growth of multiple delaminations in curved composite structures. (February 2022) - Börjesson, Elias; Remmers, Joris J.C.; Fagerström, Martin
Highlights: Adaptive isogeometric shell element for modelling multiple delamination in laminates. Stress recovery method for accurate prediction of 3D-stresses in curved shells. Robust simulation of snap-back behaviour using dissipation-based arc-length solver. Abstract: In order to model prominent failure modes experienced by multi-layered composites, a fine through-thickness discretisation is needed. If the structure also has large in-plane dimensions, the computational cost of the model becomes large. In light of this, we propose an adaptive isogeometric continuum shell element for the analysis of multi-layered structures. The key is a flexible and efficient method for controlling the continuity of the out-of-plane approximation, such that fine detail is only applied in areas of the structure where it is required. We demonstrate how so-called knot insertion can be utilised to automatise an adaptive refinement of the shell model at arbitrary interfaces, thereby making it possible to model multiple initiation and growth of delaminations. Furthermore, we also demonstrate that the higher-order continuity of the spline-based approximations allows for an accurate recovery of transverse stresses on the element level, even for doubly-curved laminates under general load. With this stress recovery method, critical areas of the simulated structures can be identified, and new refinements (cracks) can be introduced accordingly. In a concluding numerical example of a cantilever beam with two initial cracks, we demonstrate that the results obtained with the adaptive isogeometric shell element show good correlation with experimental data.